PEMBUATAN DAN UJI MUTU FISIK SEDIAAN BODY LOTION EKSTRAK KULIT BUAH RAMBUTAN (Nephelium lappaceum L) SEBAGAI ANTIOKSIDAN - burhamin, yusriyani; Syarifuddin; Nanda Putri (Jurnal Kesehatan Yamasi Makassar, 2024)
Abstract. This study aims to determine the manufacture and physical quality test of the body lotion preparation of Rambutan skin extract (Nephelium lappaceum L). The research method used was experimental laboratory by conducting experiments to manufacture body lotion preparations and testing the physical quality of the preparation which was carried out at the Pharmaceutical Laboratory of the Yamasi Pharmacy Academy, Makassar. Rambutan Skin (Nephelium lappaceum L) were extracted by maceration for using ethanol as solvent. The made body lotion preparation with a concentration of 0,1% b/b and 1% b/b. Physical quality tests carried out were organoleptic test, homogeneity test, pH test, dispersion test and adhesion test. The results showed that Rambutanskin extract (Nephelium lappaceum L) with a concentration of 0,1% b/b and 1% b/b can be made into a body lotion preparation and the physical quality test requirements of good body lotion preparations.